2004
DOI: 10.1007/s00467-003-1399-3
|View full text |Cite
|
Sign up to set email alerts
|

5-Lipoxygenase and leukotriene A 4 hydrolase expression in primary nephrotic syndrome

Abstract: Gene expression of 5-lipoxygenase (5-LO) and leukotriene A(4) (LTA(4)) hydrolase was analyzed in the peripheral blood of 48 children with active primary nephrotic syndrome (PNS) (group I), 27 children with PNS in remission (group II), and 20 controls. Group I included 34 patients with steroid-sensitive PNS (SSNS) and 14 patients with steroid-resistant PNS (SRNS). Total RNA purified from peripheral blood mononuclear (PBMN) cells was reverse transcribed into cDNA and amplified with specific primers in the polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…20 During glomerular inflammation, LTs have been detected in the urine, serum, and renal tissue. 21,22 Bakr et al 23 found a significant correlation between the expression of 5-LO and LTA 4 hydrolase and degree of proteinuria in active NS cases. Similarly, Rifai et al 24 found that proteinuria was significant in patients who express 5-LO and LTA 4 hydrolase when compared with those who had no enzyme expression in the renal tissue.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…20 During glomerular inflammation, LTs have been detected in the urine, serum, and renal tissue. 21,22 Bakr et al 23 found a significant correlation between the expression of 5-LO and LTA 4 hydrolase and degree of proteinuria in active NS cases. Similarly, Rifai et al 24 found that proteinuria was significant in patients who express 5-LO and LTA 4 hydrolase when compared with those who had no enzyme expression in the renal tissue.…”
Section: Discussionmentioning
confidence: 94%
“…In peripheral blood mononuclear cells of 48 children with active PNS, 27 children in remission, and 20 controls, Bakr et al 23 studied the gene expression of 5-LO and LTA 4 hydrolase. All patients in the active PNS group expressed 5-LO and LTA 4 hydrolase and none in the controls.…”
Section: Discussionmentioning
confidence: 99%
“…The relative enrichment of LDL in 5-HETE while being depleted in HODEs would argue for selectivity in either the production or the transport of these lipids. Notably, it has been reported that 5-lipoxygenase activity and 5-HETE levels are elevated in nephrotic and proteinuric human kidneys (34,35), and that 5-lipoxygenase inhibitors can ameliorate proteinuria (35)(36)(37)(38). Regardless, HDL carried the greatest oxidized lipid load in both control and nephrotic rats, whereas VLDL displayed the greatest proteinuria-induced changes in lipoprotein oxylipids.…”
Section: Discussionmentioning
confidence: 98%